Wave Propagation Properties of a One‐Dimensional Photonic Crystal with Double Negative Metamaterial. Issue 1 (23rd February 2023) - Pandey, Alok Kumar; Pandey, Girijesh Narayan; Kumar, Narendra; Suthar, Bhuvneshwer; Pandey, J. P.
Abstract: In this simulation work, the wave vector and reflectance properties of a 1DPC made of dielectric/metamaterial multilayer structure employing TMM, for TE and TM modes are studied. For TE mode, it is observed that the obtained wide bandgap increases with increase in the angle of incidence, whereas the narrow bandgap also shows a minor increase with increase in the incident angle. It is noted that bandgap increases with increase in the incident angle in TE mode, while bears opposite behavior in TM mode and decreases with increase in the incident angle. If the DPS thickness is increased, the number of bands increases in both TE and TM modes, while the wide bandgaps for TE and TM decreases in width. In both cases of the increased DPS width, it is found that the narrow bandgap obtained in TM mode is showing enhancement with an increase in incident angle, and exhibits ultra‐tunable behavior. Some other researchers have reported earlier that a complementary split‐ring resonator based metamaterial  with effective medium ratio has influence on the extraction of effective permittivity, permeability, and refractive index, where DNG regions exist in the ranges 6.34–7.39  and 8.20–9.98  GHz. Comparing with the proposed DNG, the study finds that the aforesaid values correspond to frequency regime taken in our case, 1–10 GHz, particularly the middle of the range 1–10 GHz, where broadband is obtained, which is satisfactory. The insights included in the article can be employed in designing microwave broadband reflectors, tunable mirrors, and can be proved to be useful in photovoltaic cells. Such PC can also be employed in designing super lenses as well as optical cloaking, and the miniaturization of antennas.